Ecologia das interações entre aranhas, formigas e Qualea multiflora (Vochysiaceae) no Cerrado: diversidade e abundância de predadores e seus impactos sobre herbívoros e herbivoria - Domingues, Larissa Nahas (2011)
Spiders and ants are among the main predators of herbivores in terrestrial trophic chains, and can indirectly benefit plants. Several plant species offer feeding resources and/or shelter to predators which provide protection against their natural enemies. The extrafloral nectar is a liquid feeding resource common in cerrado plants that attract ants and other arthropods, such as spiders for example. However, interactions between predators such as intraguild competition and predation can influence their ability to reduce herbivores and affect the final results of interactions with plants. The present study aimed to determine the impact of the spiders and ants fauna on herbivory and reproduction of Qualea multiflora (Vochysiaceae), a tree specie common in cerrado bearing paired extrafloral nectaries on the stem next to the insertion of the leaves, and on the bud pedicels. It was verified if there is difference in the effects of these two groups of predators when act jointly or separately. The field experiments were conducted in a cerrado area in Uberlandia, MG, between August 2009 and May 2010. In August 2009, 60 individuals of Q. multiflora, similar and in the same phenological state, were tagged and raffled off in four groups of 15 individuals: Control (plants with free access to spiders and ants); Exclusion (spiders and ants were removed from the plants); Ants (only spiders were removed) and Spiders (only ants were removed). Ants were excluded by covering the trunk with a lay of sticky resin (Tanglefoot) and spiders were excluded manually every three days. All plants were inspected three times per month from August 2009 to May 2010. In each inspection were registered the richness and abundance of herbivores, ants and spiders. Leaf area loss due to herbivory and action of mould, and gall infestation were registered monthly. To assess the predators impact on reproduction of Q. multiflora were counted the number of floral buds, fruits and potentially viable seeds produced by each plant. In the last month of experiments, all fruits were collected, measured and weighted. The results showed that the removal of one or both types of predators resulted in a significant increase in richness and abundance of herbivores and herbivory level in plants. There was evident seasonality in abundance of ants, spiders and herbivores. It were observed 21 ant species and 43 spider species foraging in the plants during the study. There was a higher richness and abundance of spiders in plants without ants. The richness and abundance of ants did not differ depending on the presence or absence of spiders. There was not difference in number of buds, fruits and seeds produced, or in the length and weight of fruits among the four treatments. This study shows the importance of consider the effects of all predators and not only a specific group to assess protection in extrafloral nectary-bearing plants.